Fourier transform infrared spectroscopic studies of diabetic rat heart crude membranes. Issue 2 (2003) - Severcan Severcan, Feride Feride; Kaptan Kaptan, Neşe Neşe; Turan Turan, Belma Belma
Abstract : Application of mid infrared spectroscopy in diabetic tissues will be presented which highlight the promise of this technique in medical research. Examples presented mainly will focus on diabetic rat heart crude membranes. Diabetes mellitus (DM) was induced in rats by streptozotocin (STZ) injection that is one of the most popular experimental models for the study of type I diabetes. The shift in the peak positions, bandwidths and the intensity of the bands in FTIR spectra were analyzed to have valuable structural and functional information, which may have diagnostic value. In the diabetic membranes significant increase was observed in lipid order and lipids concentration. While the concentration of saturated lipids increases, the concentration of unsaturated lipids decreases. In addition, broadening of the amide I bands and the appearance of the new band around 1640 cm −1 together with the decrease in the amide I to amide II ratio indicate the structural changes occurring in proteins of diabetic membranes. A dramatic increase in oligosaccarite band (1042 cm −1 ) and a decrease in olefinic stretching band (3012 cm −1 ), were also observed.